(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
Degenerative changes in the lumbar spine are a common reason for rehabilitation interventions. Rehabilitation is an important part of a conservative treatment program for nonspecific back pain. Due to its analgesic effect, it reduces the number of medications, improves functional capacity, and is aimed at preventing relapses. The aim of the study was to evaluate the effectiveness of rehabilitation methods used in patients with degenerative changes in the lumbar spine. The study was conducted in two groups of patients. In the first group, hardware physiotherapy, physical therapy, and water exercises were used, and in the second group, hardware physiotherapy, physical therapy, spinal traction, and water exercises were used. The effectiveness of complex therapy was assessed using the Oswestry questionnaire, the VAS scale, and functional tests: the Schober test, the Laseg test, and the Biering-Sorensen test. There was a decrease in pain in both groups (p<0.001). The decrease in the disability index was approximately 10 points in both groups. Mobility of the lumbar spine improved by an average of 1.78 cm in group II and 1.61 cm in group I. In both groups, there was a decrease in the number of patients with neurological manifestations. The obtained results of the selected functional tests did not depend on the nature of the physiotherapy treatment. The largest difference between the groups in favor of the first group was recorded in the Lassegue test, but it was not statistically significant. There were no significant differences in the results between the groups, except for a more pronounced analgesic effect of therapy in group I (p=0.032). Physiotherapeutic methods have comparable efficacy in improving the condition of patients with degenerative changes in the lumbar spine. As a result of physiotherapeutic intervention, disability and pain syndrome are reduced. The results of the selected functional tests did not depend on the type of rehabilitation intervention.